Pengaruh variasi kecepatan putar dan diameter tool terhadap sifat mekanik sambungan fssw aluminium alloy 5052 dan baja ss400 - Wahid Ramadhan; Nurul Muhayat; T Triyono (Mekanika: Majalah Ilmiah Mekanika, 2018)
Friction stir spot welding (FSSW) is a development from solid state welding to jointa different materials (dissimilar). Dissimilar FSSW is widely used in the automotive industry due to the advantages of joining these two materials with weight savings while exploiting the best strength. This research aims to know the effect of welding parameters of rotation speed and tool diameter on mechanical properties on dissimilar FSSW aluminum alloy 5052 and SS400 steel. Variations in rotational speed used is 800, 1250, 1600, 2000 rpm and tool diameter 10, 12, 14 mm. Plunge depth and dwell time in this research were made uniform. This research used a lap joint configuration with aluminum plate placed on the top and steel plate placed on the bottom. Physical characteristics were analyzed through observation of macro and microstructures, while mechanical characteristics through vickers hardness testing and shear tensile testing. The results indicate that the diameter of 10 mm tool and 1600 rpm rotation speed produce the highest tensile shear load value of 2.4 kN with interface fracture.